ChemInform Abstract: Investigation of Oxidopyrylium—Alkene [5 + 2] Cycloaddition Conjugate Addition Cascade (C3) Sequences. Issue 2 (January 2015) - Simanis, Justin A.; Law, C. Marshall; Woodall, Erica L.; Hamaker, Christopher G.; Goodell, John R.; Mitchell, T. Andrew
Abstract A series of bridged tetracyclic ethers is prepared with high diastereoselectivity via a novel oxidopyrylium—alkene cycloaddition—conjugate addition cascade reaction of readily accessible acetoxypyranone‐alkenes.